Effect of Aqueous Extract of Cathedral Cactus (Euphorbia trigona Mill) on Larvae of Anopheles arabiensis (Diptera: Culicidae) - Kehail, mutaman A A.; Abdalla, Abdalla I.; Musa Abdelah, Hufsa Ebrahim (Gezira Journal of Health Sciences, 2016)
Abstract: Mosquitoes are considered as vector of malaria disease and some other endemic diseases in the world. There are some methods already been used for controlling mosquito; of which is using natural products. This study was conducted at Laboratories of Faculty of Engineering and Technology, University of Gezira, to evaluate the effect of cortex, spine and pith parts of cactus ( Euphorbia trigona ) on Anopheles mosquito larvae. The plant parts were collected from Wad Medani City, whereas, the mosquito larvae were collected from the breeding sites at Tayba village, Gezira State, Sudan. The plant parts (cortex, spines and pith) were shade dried away from the direct sunlight, grounded and then kept separately in small plastic sacks. From each plant part, a concentration of 1200 mg/L was used. The standards of WHO for testing toxicity of the toxic compound against mosquito larvae was followed. The mortality in Anopheles larvae were 48%, 37% and 62%, respectively, for trigona cortex, spine and pith. The results also showed that, the three used parts have a varied great impact on the survived larvae (morphological changes of skin color was in 82%, disconnecting of digestive tract was in 48%, and separation of some body parts was in 32%, after 48 hours of applying it). The study recommends adding these cactus parts as potential natural products for Anopheles larval control, and also running more sensitive tests to measure the environmental impact of these products, especially on human and on the aquatic fauna